The concentration of energy from Edge Lasers by Diffractive Optical Component - Sobczyk, Artur; Suszek, Jarosław; Kołodziejczyk, Andrzej; Sypek, Maciej (Photonics Letters of Poland, 2016)
The aim of this paper is to design a diffractive optical element based on the laser junction numerical model. We assumed a ?long? laser junction emitting quasi-monochromatic, spatially incoherent light that corresponds to the high power laser. Diffractive optics approach can be used due to the narrowband illumination. The especially designed numerical junction model was experimentally verified. Then a numerically designed diffractive focusing element was manufactured and tested in the experimental setup. This paper includes theoretical investigations, numerical modeling as well as experimental data. Full Text: PDF References E. Wolf, "New theory of partial coherence in the space?frequency domain. Part I: spectra and cross spectra of steady-state sources", J. Opt. Soc. Am. 72, 343 (1982). CrossRef E. Wolf, "Coherence theory of laser resonator modes", J. Opt. Soc. Am. A 1, 541 (1984). CrossRef A. Naqwi and F. Durst, "Focusing of diode laser beams: a simple mathematical model", Appl. Opt. 29, 1780 (1990) CrossRef J. Yang, T. Chen, G. Ding and X. Yuan, "Focusing of diode laser beams: a partially coherent Lorentz model", Proc. SPIE 6824, 68240A (2007); CrossRef X. Zeng and A. Naqwi, "Far-field distribution of double-heterostructure diode laser beams", Appl. Opt. 32, 4491 (1993). CrossRef Y. Li and J. Katz, "Nonparaxial analysis of the far-field radiation patterns of double-heterostructure lasers", Appl. Opt. 35, 1442 (1996). CrossRef X. Zeng, Z. Feng, and Y. An, "Far-field expression of a high-power laser diode", Appl. Opt. 43, 5168 (2004) CrossRef J. Tervo, J. Turunen, P. Vahimaa, and F. Wyrowski, "Shifted-elementary-mode representation for partially coherent vectorial fields", J. Opt. Soc. Am. A 27, 2004 (2010). CrossRef J. Turunen, "Elementary-field representations in partially coherent optics", J. Mod. Opt. 58, 509 (2011). CrossRef H. Partanen, J. Tervo, and J. Turunen, "Spatial coherence of broad-area laser diodes", Appl. Opt. 52, 3221 (2013) CrossRef M. Sypek, "Light propagation in the Fresnel region. New numerical approach", Opt. Commun., 116, 43 (1995) CrossRef Z. Jaroszewicz, A. Kołodziejczyk, M. Sypek, C. Gomez-Reino, "Non-paraxial analytical solution for the generation of focal curves", J. Mod. Opt., 43, 617 (1996) CrossRef M. Sypek, C. Prokopowicz, M. Górecki, "Image multiplying and high-frequency oscillations effects in the Fresnel region light propagation simulation", Opt. Eng., 42, 3158 (2003) CrossRef C. Prokopowicz, "Numerical calculation of light propagation in off-axis region", Proc. SPIE, 5484, 482 (2004). CrossRef A. Sobczyk, Z. Jaroszewicz, A. Kolodziejczyk, A. Kowalik, Cz. Prokopowicz, M. Sypek, "Nonparaxial anamorphic diffractive lenses", J. Opt., 15, 025702 (1-5) (2013) CrossRef